2017
DOI: 10.3389/fphys.2017.00127
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Signature of an Altered Purine Metabolism in the Skeletal Muscle of a Huntington's Disease Mouse Model

Abstract: Huntington's disease (HD) is a fatal neurodegenerative disorder, caused by a polyglutamine expansion in the huntingtin protein (HTT). HD has a peripheral component to its pathology: skeletal muscles are severely affected, leading to atrophy, and malfunction in both pre-clinical and clinical settings. We previously used two symptomatic HD mouse models to demonstrate the impairment of the contractile characteristics of the hind limb muscles, which was accompanied by a significant loss of function of motor units.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…First, AMPD3 is a cytosolic enzyme that mediates the thermodynamically irreversible deamination of AMP to IMP. AMPD3 mRNA is reported to be one of the most upregulated genes in atrophying muscles from cancer [149], diabetes [149], renal failure [150], aging [151], Huntington's disease [152], fasting [149,153], unloading [154], and denervation [153,155,156]. However, AMPD3 expression has not been reported to increase in muscular dystrophy.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…First, AMPD3 is a cytosolic enzyme that mediates the thermodynamically irreversible deamination of AMP to IMP. AMPD3 mRNA is reported to be one of the most upregulated genes in atrophying muscles from cancer [149], diabetes [149], renal failure [150], aging [151], Huntington's disease [152], fasting [149,153], unloading [154], and denervation [153,155,156]. However, AMPD3 expression has not been reported to increase in muscular dystrophy.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…One of the most studied peripheral pathologies in HD is skeletal muscle atrophy (reviewed in Zielonka et al, 2014a ; Mielcarek and Isalan, 2015 ; Mielcarek et al, 2015a , 2017 ). In fact, a recent study showed that rescuing skeletal muscle degeneration alone had a profound therapeutic effect in HD model mice.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works from other groups reported changes in NMJs and muscles in R6/2 mouse model for HD that could be related to motoneurons degeneration (Ribchester et al, 2004;Mielcarek and Isalan, 2015;Khedraki et al, 2017). However, these authors did not look at the spinal cords to address whether motoneurons were indeed affected in R6/2 mice.…”
Section: Discussionmentioning
confidence: 96%
“…Menalled et al, 2009;Yang and Gray, 2011). Experiments performed in these animal models allowed the identification of mutant huntingtin protein (mHTT) not only in the CNS but also in peripheral structures, such as skeletal muscles (van der Burg et al, 2009;Zielonka et al, 2014;Mielcarek et al, 2017). In fact, mouse HD models exhibited pronounced skeletal muscle atrophy, a pathophysiological finding that could be due to accumulation of mHTT in skeletal muscles, motoneurons, or both (Khedraki et al, 2017).…”
Section: Introductionmentioning
confidence: 99%